Convenient conversion of hazardous nitrobenzene derivatives to aniline analogues by Ag nanoparticles, stabilized on a naturally magnetic pumice/chitosan substrate. Issue 71 (8th December 2020) - Taheri-Ledari, Reza; Mirmohammadi, Seyedeh Shadi; Valadi, Kobra; Maleki, Ali; Shalan, Ahmed Esmail
Abstract : Silver nanoparticles (Ag NPs), as an effective catalyst for the reduction process of nitrobenzene derivatives to non-hazardous and useful aniline derivatives, are conveniently synthesized on an inherently magnetic substrate. Abstract : Herein, silver nanoparticles (Ag NPs), as an effective catalyst for the reduction process of nitrobenzene derivatives to non-hazardous and useful aniline derivatives, are conveniently synthesized on an inherently magnetic substrate. For this purpose, an efficient combination of volcanic pumice (VP), which is an extremely porous igneous rock, and a chitosan (CTS) polymeric network is prepared and suitably used for the stabilization of the Ag NPs. High magnetic properties of the fabricated Ag@VP/CTS composite, which have been confirmed via vibrating-sample magnetometer (VSM) analysis, are the first and foremost advantage of the introduced catalytic system since it gives us the opportunity to easily separate the particles and perform purification processes. Briefly, higher yields were obtained in the reduction reactions of nitrobenzenes (NBs) under very mild conditions in a short reaction time. Also, along with the natural biocompatible ingredients (VP and CTS) in the structure, excellent recyclability has been observed for the fabricated Ag@VP/CTS catalytic system, which convinces us to do scaling-up and suggests the presented system can be used for industrial applications.